2013
DOI: 10.1136/bcr-2013-010844
|View full text |Cite
|
Sign up to set email alerts
|

Direct puncture sclerotherapy of a thoracic duct cyst presenting as an enlarging left supraclavicular mass

Abstract: A 58-year-old woman presented with a palpable mass at the base of the left neck which she had first noticed 12 years previously, shortly after abdominal surgery. The mass had progressively enlarged, resulting in dysphagia, dyspnea and occasional pain. Imaging showed a septated but otherwise simple cystic mass extending into the mediastinum and containing lymphocytic fluid on aspiration. A diagnosis of the rare entity of a thoracic duct cyst with supraclavicular extension was made. The patient opted for percuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…They commonly present as a mass in the supraclavicular fossa as soft, fluctuant and mobile. This can be accompanied by symptoms which include dyspnoea, dysphagia and hoarse voice because of pressure of the mass on closely associated structures 6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They commonly present as a mass in the supraclavicular fossa as soft, fluctuant and mobile. This can be accompanied by symptoms which include dyspnoea, dysphagia and hoarse voice because of pressure of the mass on closely associated structures 6…”
Section: Discussionmentioning
confidence: 99%
“…Fluid aspirated from the cyst appears milky or pale yellow depending on its proportion of protein and triglycerides. Kadkhodayan et al 6 revealed that lymph from the upper abdomen consists of a milky appearance in comparison to a pale yellow appearance of lymph from the retroperitoneum and pelvis.…”
Section: Discussionmentioning
confidence: 99%
“…The majority described aspiration of milky fluid from the cystic swelling which on biochemical tests yielded a significant amount of triglycerides and chylomicrons. Kadkhodayan et al[10], however, reported aspirating straw-coloured rather than milky fluid from CTDC, and it was postulated to come from lymphatic drainage of the retroperitoneum and pelvis rather than from the gut and upper abdomen.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Possible complications of sclerotherapy include fever and localized tenderness, but these could be controlled by non-steroidal anti-inflammatory drugs (NSAIDs). Kadkhodayan et al [10]used half of the equivalent aspirated volume of a sclerosant mixture consisting of 50% glacial acetic acid, 25% contrast, and 25% saline under fluoroscopy-guidance and allowed to stay for 5 min before aspiration. A short follow-up of 6 weeks showed resolution of symptoms.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…However, it is less helpful in distinguishing these lesions among "mimickers", such as pericardial, pleural mesothelial, bronchial, esophageal duplication or neurogenic cysts (6). The recommended treatment remains surgical resection although direct puncture sclerotherapy was recently reported to be an optional method (7,8). However, the long term effect still needs to be evaluated.…”
Section: Discussionmentioning
confidence: 99%